Health and economic assessment of ultrafine particles in Stockholm: impacts of electrification and local policies - Broman, Lina; Engardt, Magnuz; Silvergren, Sanna; Kriit, Hedi; Norman, Michael; Johansson, Christer (Environment international, 2025)
High resolution air quality dispersion modelling was applied to assess the health risks of long-term exposure to ultrafine particles (UFP) emitted from the transport sector and to evaluate the health benefits of different local interventions in Stockholm. Health impacts, based on associations between exposure, premature mortality and various diseases, were quantified as quality adjusted life years (QALYs) and monetized as health-related costsIrrespective of local mitigation measures in the city, fleet renewal driven byvehicle emission regulations is projected to reduce UFP exposure by 86 % between 2021 and 2030, saving almost 1700 QALYs corresponding to approximately €500 M in health-related costs. The renewal of the fleet affects mainly diesel passenger cars and heavy goods diesel vehicles equipped with particle filters, whichefficiently remove most exhaust particles, including UFPs. Among the local mitigation policies, the introduction of a low emission zone (LEZ) in 2030 covering 16 km2 of the inner city is estimated to save around 40 QALYs. In contrast, a much smaller LEZ (0.2 km2) approved by the city council would yield minimal health benefits, saving only 0.1 QALYs. Electrification of road vehicles under the business as usual (BAU) scenario is projected to save around 70 QALYs in 2030, exceeding the gains of any local policy scenario. Comparisons using PM2.5 and NO2 as predictors of health-related emissions, shows that gains in adverse health impacts of local mitigation actions may be severely underestimated if only health impacts of UFP exposure is considered.